UPAYA MEMOTIVASI KREATIVITAS BELAJAR DENGAN MODEL PEMBELAJARAN PICTURE AND PICTURE - Dermawati, Dermawati (JURNAL PENA EDUKASI, 2018)
Abstract: Classroom action research in general aims to improve the quality of learning for second grade students of SD Negeri 017141 Perk. Gunung Melayu, specifically aimed at: 1. Efforts to Motivate Learning Creativity with the Application of Picture and Picture Methods Main Material Important Events in Family Social Studies Lessons Class II SD Negeri 017141 Perk. Gunung Melayu district Rahuning academic year 2016/2017; 2. Describe the management of social studies learning by teachers; This classroom action research is carried out in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. This classroom action research was conducted in class II SD Negeri 017141 Perk. Gunung Melayu totaling 25 students. The subjects of this study were class II teachers and second grade students SDN 017141 Perk. Gunung Melayu, data was collected through observation, interviews, tests, and documentation studies. Keyword: Motivating Learning Creativity, Picture and Picture Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas II SDN 017141 Perk. Gunung Melayu. secara khusus bertujuan untuk : 1. Upaya Memotivasi Kreativitas Belajar Dengan Penerapan Metode Picture and Picture Materi Pokok Peristiwa Penting Dalam Keluarga Pelajaran IPS Kelas II SDN 017141 Perk. Gunung Melayu Kec. Rahuning TP. 2016/2017; 2. Mendeskripsikan pengelolaan pembelajaran IPS oleh guru ; Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas ini dilaksanakan dikelas II SDN 017141 Perk. Gunung Melayu yang berjumlah 25 orang siswa. Subjek penelitian ini adalah guru kelas II dan siswa kelas II SDN 017141 Perk. Gunung Melayu, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata kunci: Memotivasi Kreativitas Belajar, Picture and Picture